2020
DOI: 10.17644/sbd.669792
|View full text |Cite
|
Sign up to set email alerts
|

Consumption of Sports and Energy Drinks in Different Sports Branches and Their Effects on Performance

Abstract: Sporcularda sıvı dengesinin sağlanamaması ve glikojen depolarının tükenmesi, yorgunluğa neden olarak performansı olumsuz etkilemektedir. Yorgunluğun azaltılarak optimal spor performansının sağlanabilmesi için çeşitli beslenme stratejileri geliştirilmiştir. Spor içecekleri hem sıvı dengesinin korunmasına yardımcı olarak dehidrasyonu önlediği, hem de egzersiz anında substrat ve elektrolit desteği sağladığı için egzersiz yapan bireyler tarafından yaygın olarak kullanılan beslenme destekleridir. Spor içecekleri te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 85 publications
0
2
0
Order By: Relevance
“…In addition to their positive effects on human health, it has been shown in various studies that they may have negative effects and may lead to dental caries [10][11][12]. It has also been reported that energy drink consumption can lead to health problems such as central nervous system disorders (headache, anxiety, nervousness, agitation, dizziness), obesity, cardiovascular problems (heart palpitations, chest pain, increased heart rate and hypertension), platelet-related diseases, electrolyte-related renal problems [13].…”
Section: Figure 1 Some Energy Drinks Sold On Market Shelves Under Dif...mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to their positive effects on human health, it has been shown in various studies that they may have negative effects and may lead to dental caries [10][11][12]. It has also been reported that energy drink consumption can lead to health problems such as central nervous system disorders (headache, anxiety, nervousness, agitation, dizziness), obesity, cardiovascular problems (heart palpitations, chest pain, increased heart rate and hypertension), platelet-related diseases, electrolyte-related renal problems [13].…”
Section: Figure 1 Some Energy Drinks Sold On Market Shelves Under Dif...mentioning
confidence: 99%
“…The lack of sufficient knowledge on their health effects raises concerns about the risks associated with high doses. It is thought that more experimental, clinical and laboratory studies on energy drinks will fill this gap [13,14].…”
Section: Figure 1 Some Energy Drinks Sold On Market Shelves Under Dif...mentioning
confidence: 99%